2013
DOI: 10.1523/jneurosci.5673-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Central Dopamine D2 Receptors Regulate Growth-Hormone-Dependent Body Growth and Pheromone Signaling to Conspecific Males

Abstract: Competition between adult males for limited resources such as food and receptive females is shaped by the male pattern of pituitary growth hormone (GH) secretion that determines body size and the production of urinary pheromones involved in male-to-male aggression. In the brain, dopamine (DA) provides incentive salience to stimuli that predict the availability of food and sexual partners. Although the importance of the GH axis and central DA neurotransmission in social dominance and fitness is clearly apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 39 publications
2
48
0
1
Order By: Relevance
“…Even though brain dopamine 2 receptors (D2R) regulate pituitary function and are required for full development of the body growth plan (11), the role of dopamine medications on liver dimorphic gene expression has received little attention. Central D2Rs participate not only in control of locomotor activity, executive planning, motor coordination, pain perception, food intake, aggressive and reward-seeking behaviors, but also in the regulation of the GHRH-GH axis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though brain dopamine 2 receptors (D2R) regulate pituitary function and are required for full development of the body growth plan (11), the role of dopamine medications on liver dimorphic gene expression has received little attention. Central D2Rs participate not only in control of locomotor activity, executive planning, motor coordination, pain perception, food intake, aggressive and reward-seeking behaviors, but also in the regulation of the GHRH-GH axis (12).…”
mentioning
confidence: 99%
“…Furthermore, lactotrope D2Rs mediate the tonic inhibition that dopamine exerts on prolactin synthesis and release (13), while in the periphery, dopamine regulates pancreatic endocrine function including insulin release from pancreas, and its action on adipocytes (14,15). A link has been established between obesity, growth and dopaminergic systems located both within the central nervous system (CNS) or in other tissues (11,16,17). Therefore, the complex and integral analysis of the dopaminergic function indicates that the D2R plays key roles in the multifaceted repertoire of adaptive functions that improve fitness, reproductive success, and survival.…”
mentioning
confidence: 99%
“…Recent in vivo studies, using genetically modified mice that lack dopamine D2 receptors (Drd2 À/À ), revealed dopamine as a crucial regulator of growth-hormone-dependent body growth. Drd2 À/À mice exhibit deficiency of pituitary somatotrophs associated with decreased growth hormone and IGF-1 serum levels, ultimately resulting in dwarfism (Díaz-Torga et al 2002;Noaín et al 2013). In addition, mice deficient in the SPR gene (Spr À/À ) display a phenotype comparable to Drd2 À/À mice with severely reduced concentrations of IGF-1 in serum and growth retardation (Yang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Social dominance behaviour may be especially sensitive to changes in the level of DA. The disruption of dopaminergic transmission increases competition and social dominance (Nader et al 2012;Noain et al 2013). Therefore, it is possible that clozapine suppresses social dominance behaviour by enhancing DA release and reduces the disruption of dopaminergic transmission.…”
Section: Discussionmentioning
confidence: 99%